2004
DOI: 10.1124/jpet.104.071423
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Receptor Like-1 Receptor Agonist Ro 64-6198 (1S,3aS-8-2,3,3a,4,5,6-Hexahydro-1H-phenalen-1-yl-1-phenyl-1,3,8-triaza-spiro[4.5]decan-4-one) Produces a Discriminative Stimulus in Rats Distinct from That of a μ, κ, and δ Opioid Receptor Agonist Cue

Abstract: Male Wistar rats were trained to discriminate either the opioid receptor like (ORL)-1 receptor agonist 3,3a,4,5,3,decan-4-one) or morphine from saline using a twochoice, food reinforced, operant procedure. Acquisition of Ro 64-6198 discrimination was relatively slow (mean trials to criterion 113 Ϯ 6), and a final 4 mg/kg dose (initial training dose 2 mg/kg) was required to establish appropriate stimulus control. In comparison, a separate group of rats attained a morphine (2 mg/kg) discrimination in 44 Ϯ 4 tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The anxiolytic effect was attenuated by the NOP receptor antagonist J-113397, which had no effects on punished drinking per se. Although in our hands, the anxiolytic effects of Ro 64-6198 were only partially blocked by J-113397, this data confirm previous pharmacological evidence, with J-113397 (Ko et al 2009;Recker and Higgins 2004;Varty et al 2005) as well as genetic evidence in NOP receptor knockout animals (Higgins et al 2001;Reiss et al 2008;Varty et al 2005), indicating that the behavioral effects of the currently used doses of Ro 64-6198 are exclusively mediated by the NOP receptor. Moreover, it is unlikely that the anxiolytic properties of Ro 64-6198 in the VCT are related to other NOP receptor-mediated functions such as pain control or diuresis (for review see Chiou et al 2007, Shoblock 2007.…”
Section: Discussionsupporting
confidence: 92%
“…The anxiolytic effect was attenuated by the NOP receptor antagonist J-113397, which had no effects on punished drinking per se. Although in our hands, the anxiolytic effects of Ro 64-6198 were only partially blocked by J-113397, this data confirm previous pharmacological evidence, with J-113397 (Ko et al 2009;Recker and Higgins 2004;Varty et al 2005) as well as genetic evidence in NOP receptor knockout animals (Higgins et al 2001;Reiss et al 2008;Varty et al 2005), indicating that the behavioral effects of the currently used doses of Ro 64-6198 are exclusively mediated by the NOP receptor. Moreover, it is unlikely that the anxiolytic properties of Ro 64-6198 in the VCT are related to other NOP receptor-mediated functions such as pain control or diuresis (for review see Chiou et al 2007, Shoblock 2007.…”
Section: Discussionsupporting
confidence: 92%
“…94 This discriminative stimulus was not as strong as that produced by mu opioid agonists, suggesting that NOP agonists are likely to be devoid of reinforcing or euphorigenic effects. In nonhuman primates, 8 did not produce reinforcing effects at doses at which it showed significant antinociceptive effects.…”
Section: Introductionmentioning
confidence: 93%
“…Rats trained to discriminate Ro 64-6198 from saline, morphine 6 mg/kg, and buprenorphine 0.1 mg/kg, produced 40%-50% responding on the drug-appropriate lever, but these doses significantly suppressed rates of responding, and there was considerable variability among subjects (Recker and Higgins, 2004). This is consistent with the present study in that Ro 64-6198-trained monkeys responded on the drug-appropriate lever when tested with doses of fentanyl and buprenorphine that also suppressed rates of responding, except that neither drug met criteria for generalization.…”
Section: Stimulus Effects Of Ro 64-6198 In Rhesus Monkeysmentioning
confidence: 99%
“…Previous research has established that agonist stimulation of MOP, DOP, and KOP produced discriminative stimulus effects that are pharmacologically selective Colpaert, 1999). Previous drug discrimination studies with Ro 64-6198 in rats showed that it possessed stimulus properties that were unlike opioid agonists at MOP, DOP, and KOP (Recker and Higgins, 2004). These effects were selectively blocked with the NOP antagonist, J-113397, but not with the opioid antagonist naltrexone.…”
Section: Introductionmentioning
confidence: 99%